The Contribution of Various MRI Parameters to Clinical and Cognitive Disability in Multiple Sclerosis - Tóth, Eszter; Faragó, Péter; Király, András; Szabó, Nikoletta; Veréb, Dániel; Kocsis, Krisztián; Kincses, Bálint; Sandi, Dániel; Bencsik, Krisztina; Vécsei, László; Kincses, Zsigmond Tamás (Frontiers in Neurology, 2019)
Next to the disseminated clinical symptoms, cognitive dysfunctions are common features of multiple sclerosis (MS). Over the recent years several different MRI measures became available representing the various features of the pathology, but the contribution to various clinical and cognitive functions is not yet fully understood. In this multiparametric MRI study we set out to identify the set of parameters that best predict the clinical and cognitive disability in MS. High resolution T1 weighted structural and high angular resolution diffusion MRI images were acquired in 53 relapsing remitting MS patients and 53 healthy controls. Clinical disability was measured by EDSS and cognitive functions were evaluated with the BICAMS tests. The contribution of lesion load, total brain, white matter, grey matter and subcortical volumes as well as the diffusion parameters of the lesions and the normal appearing white matter were investigated by model free, partial least square (PLS) approach. Significance of the predictors was tested with Variable Importance in the Projection (VIP) score and 1 was used for threshold of significance. The PLS analysis indicated that the axial diffusivity of the NAWM contributed the most to the clinical disability. For the visuo-spatial working memory the most critical contributor was the size of the bilateral hippocampi (VIP scores: 1.5 and 1.68 left and right respectively) For the verbal memory the best predictor was the size of the right hippocampus (VIP=1.96) and the total grey matter volume (VIP=1.74). In case of the information processing speed the most significant contribution was from the diffusion parameters (fractional anisotropy, mean and radial diffusivity, VIP scores: 1.85, 1.46, 1.77 respectively) of the normal appearing white matter. Our results indicate that various MRI measurable factors of MS pathology contribute differently to clinical and cognitive disability. These results point out the importance of the volumetry of the subcortical structures and the diffusion measures of the white matter in understanding the disability progression.